Determining the nurses’ perception regarding the effectiveness of COVID-19 protocols implemented in Eastern Province: Saudi Arabia - Aljaffary, Afnan; Al Elaiwi, Tahani; AlOtaibi, Noot; AlAnsari, Fatimah; Alumran, Arwa; Salama, Khaled F. (Frontiers in Public Health, 2024)
The global impact of Coronavirus Disease 2019 (COVID-19) has been profound, affecting public health, the global economy, and overall human life. Past experiences with global pandemics underscored the significance of understanding the perception of HCWs and hospital staff in developing and implementing preventive measures. The World Health Organization (WHO) provided protocols to manage the spread of COVID-19 and assist healthcare workers and health systems globally in maintaining high-quality health services.Objective: This study aims to assess nurses' perception, awareness, and compliance regarding the implementation of COVID-19 protocols and explore factors influencing their perception.Methodology: A quantitative cross-sectional survey-based study was conducted, distributing a constructed survey among nurses in the Eastern province of Saudi Arabia.Results: Out of 141 participants, most adhered to protocols such as hand sanitization, social distancing, and proper personal protective equipment (PPE) usage. The predominant age group among respondents was 31 to 40 years (n= 71, 50%). A significant portion of participants reported holding a bachelor's degree (n= 86, 61%), with only 14% possessing advanced degrees (n= 19). Nearly a third of the nurses in the study had accumulated 6 to 10 years of professional experience (n= 49, 34.8%). A noteworthy percentage of nurses were engaged in daily shifts exceeding 8 hours (n= 98, 70%).Gender differences were observed, with females exhibiting a higher tendency to avoid shaking hands and social gatherings. Saudi nationals were more inclined to shake hands and engage in gatherings. Non-Saudi nurses and those aged between <25 to 40 years demonstrated proper donning/doffing practices. Nurses with over 6 years of experience avoided social gatherings, while those working >8 hours adhered better to PPE usage, proper donning/doffing, and disposal of PPE in designated bins.Understanding COVID-19 protocols is crucial for tailoring interventions and ensuring effective compliance with COVID-19 preventive measures among nurses. More efforts should be made toward preparing the healthcare nursing to deal with the outbreak.Preparing healthcare nursing with the right knowledge, attitude, and precautionary practices during the COVID-19 outbreak is very essential to patient and public safety.